Hubungan Pengetahuan Wanita Usia Subur dan Dukungan Suami Dengan Lama Penggunaan Kontrasepsi IUD (Intrauterine Device) - Fitri Dwi Rahayu; Cucuk Kunang Sari (Journal of Midwifery and Health Research, 2026)
Background: The use of long-acting contraceptive methods (LACMs), particularly the Intrauterine Device (IUD), remains relatively low despite their high effectiveness in preventing pregnancy. The low uptake of IUDs is influenced by various factors, including limited knowledge among women of reproductive age and a lack of spousal support in decision-making regarding contraceptive use. Objective: This study aims to analyse the relationship between the knowledge of women of reproductive age and spousal support with the duration of IUD use. Methods: This study employed a correlational design with a cross-sectional approach. The sample comprised 36 women of reproductive age who were IUD users, selected using purposive sampling within the catchment area of the Neglasari Community Health Centre. Data were collected via a questionnaire covering respondent characteristics, knowledge levels, and spousal support. Data analysis was conducted using univariate and bivariate methods, employing Fisher’s Exact test. Results: The findings indicate that the majority of respondents possessed good knowledge and received support from their husbands. A significant relationship was found between knowledge and the duration of IUD use, with respondents possessing good knowledge tending to use the IUD for more than two years. Furthermore, spousal support was also significantly associated with the duration of IUD use, with an Odds Ratio (OR) of 8.313, indicating that women who received spousal support were more likely to use the IUD long-term. Conclusion: Knowledge and spousal support are important factors in the continued use of the IUD; therefore, improved health education and partner involvement are required.